Comparison of Laparoscopic-Assisted Operations and Laparotomy Operations for the Treatment of Hirschsprung Disease: Evidence From a Meta-Analysis. Issue 39 (September 2015) - Zhang, Shisong; Li, Juan; Wu, Yurui; Hu, Yuanjun; Duan, Chunhong; Wang, Meiyun; Gai, Zhongtao
Abstract : Abstract: The purpose of this meta-analysis is to compare the relative merits among laparoscopic-assisted operations and laparotomy operations for patients with Hirschsprung disease. PubMed, Web of Science, and Wanfang databases were searched for the related articles. We analyzed dichotomous variables by estimating odds ratios (ORs) with their 95% confidence intervals (CIs) and continuous variables using the weighted mean difference (WMD) with the 95% CI. The random-effects model (REM) was used to combine the results. The outcome measures included operating time (OT), estimated blood loss (EBL), length of hospital stay (LOHS), mean first bowel movement (MFBM), and number of complications. Sixteen articles were included in the meta-analysis. These studies involved a total of 774 patients, 396 of whom underwent laparoscopic-assisted operations and 378 of whom underwent laparotomy operations. The EBL (WMD = −1.48, 95% CI = −1.82, −1.13), LOHS (WMD = −0.67, 95% CI = −0.86, −0.49), MFBM (WMD = −0.83, 95% CI = −1.05, −0.61), and number of complications (OR = 0.60, 95% CI = 0.40, 0.89) were significantly lower in laparoscopic-assisted operations than in laparotomy operations. The OT (WMD = 0.12, 95% CI = −0.05, 0.28) showed no significant differences between laparoscopic-assisted operations and laparotomy operations. Compared with laparotomy operations, laparoscopic-assisted operations are generally safer and more reliable for patients with Hirschsprung disease.